2016
DOI: 10.3390/rs8110895
|View full text |Cite
|
Sign up to set email alerts
|

Spaceborne Sun-Induced Vegetation Fluorescence Time Series from 2007 to 2015 Evaluated with Australian Flux Tower Measurements

Abstract: A global, monthly averaged time series of Sun-induced Fluorescence (SiF), spanning

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 84 publications
5
54
0
Order By: Relevance
“…This finding is supported by the 2016 GPP anomaly at the VCP site, for which both SIF GOME2 and SIF OCO2 time series were found to capture early season photosynthetic activity, whereas EVI and PRI did not ( Figure S6). Our results are consistent with previous studies that have demonstrated similar potential for SIF as an improved GPP proxy (Manish Verma et al, 2017;Perez-Priego et al, 2015;Sanders et al, 2016;Wood et al, 2016;Yang et al, 2017;Zarco-Tejada et al, 2016;Zhang et al, 2014), although few to our knowledge have evaluated dryland, water-limited ecosystems such as these.…”
Section: Seasonal Gpp Dynamicssupporting
confidence: 93%
“…This finding is supported by the 2016 GPP anomaly at the VCP site, for which both SIF GOME2 and SIF OCO2 time series were found to capture early season photosynthetic activity, whereas EVI and PRI did not ( Figure S6). Our results are consistent with previous studies that have demonstrated similar potential for SIF as an improved GPP proxy (Manish Verma et al, 2017;Perez-Priego et al, 2015;Sanders et al, 2016;Wood et al, 2016;Yang et al, 2017;Zarco-Tejada et al, 2016;Zhang et al, 2014), although few to our knowledge have evaluated dryland, water-limited ecosystems such as these.…”
Section: Seasonal Gpp Dynamicssupporting
confidence: 93%
“…[42,43]. Previous studies have discussed the effect of the fit window, the numbers of PCs, and the reference area for PC determination on the retrieval outcome [42,43,55]. Köhler et al depicted the standard error of the mean of GOME-2 SIF composites for January 2011, and the results showed that the standard error of the mean was generally low (<0.15 mW/m 2 /sr/nm) for GOME-2 SIF in Australia [42].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in satellite sensors and retrieval techniques have enabled remote sensing of solar-induced chlorophyll fluorescence (SIF), the natural emission of photons from the light-harvesting structures of sunlit plants, which is a biophysical consequence of light absorption. Previous work has shown that space-based SIF observations correlate significantly with GPP derived from ground-based eddy covariance, reliably predicting the monthly or average seasonal pattern of GPP for a range of biomes (Frankenberg et al, 2011;Guanter et al, 2014;Joiner et al, 2014;Sanders et al, 2015). SIF appears promising as a more physiologically meaningful proxy to photosynthesis (e.g., Yang et al, 2015) than do traditional remote sensing-based vegetation indices, such as the normalized difference vegetation index (NDVI) and the enhanced vegetation index (EVI; Myneni & Williams, 1994;Rahman et al, 2005;Shi et al, 2017;Sims et al, 2006;Xiao et al, 2004).…”
Section: Citationmentioning
confidence: 99%
“…Recent studies suggest that SIF provides information on LUE in coniferous forests (Walther et al, ; Yao Zhang et al, ), underscoring its possible advantage over traditional remote sensing indices (i.e., NDVI and EVI), which do not provide information about LUE. The slope of the GPP‐SIF relationship has shown to be biome‐specific (Damm et al, ; Guanter et al, , ; Parazoo et al, ; Sanders et al, ), but recent work with OCO‐2 SIF data suggests there may be a universal relationship (Sun et al, ). However, due to physiological and phenological differences between plant species and functional types, as well as structural complexities of vegetation canopies across the landscape, a universal relationship may prove elusive (see reviews by Gamon () and Porcar‐Castell et al ()).…”
Section: Introductionmentioning
confidence: 99%